Implementasi Balanced Scorecard Sebagai Tolak Ukur Kinerja Pada Instansi Pemerintah Daerah (Studi Kasus Pada Kecamatan Cidahu Kabupaten Kuningan) - Rahma Fidela, Nadia; Ernita Sembiring, Etti (Indonesian Accounting Research Journal, 2023)
This study aims to measure the performance of Cidahu District, Kuningan Regency with the Balanced Scorecard Method. The balanced scorecard is a method that can be used to analyze organizational performance in the financial and non-financial sectors. The purpose of this research is to build a model that is used to assess the performance of public services in a Regional Apparatus Organization (OPD). The Balanced Scorecard approach is applied to determine the hierarchy of financial perspective, customer perspective, internal business process perspective, and growth and learning perspective. This type of research is a quantitative and qualitative approach. The results of this study are that financial performance in terms of the budget has been effective and efficient with a respective percentage of 98.7% and 26.1%. Non-financial performance seen from the customer perspective shows very satisfactory results, the internal business process perspective and the growth and learning perspective show satisfactory results. However, the financial and non-financial performance still needs to be improved and improved.